A rare association of cervical tuberculosis and primary infertility in a young nulligravida female - Sah, Ravi; Deshwali, Akanksha; Yadav, Kripa; Rawat, Shriya; Reddy, Divya; Bose, Shalini; Gulati, Garvita; Kamdi, Parish; Asati, Vanshika; Perka, Manisha; Sah, Shashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Tuberculosis of the cervix is rare and may have a clinical presentation and hypertrophic growth like morphological appearance masquerading as that of cervical carcinoma. Due to nonspecific symptoms, there is often a delay in diagnosis and treatment, and thereby increasing the risk of infertility in young females. Here, we present a rare case of a 26 years young female with primary infertility and cervical tuberculosis. The patient presented with complaints of being keen to conceive for 3 years and occasional post coital spotting p/v. Her ultrasonography (USG) pelvis and hormonal analysis and her husband’s semen analysis reports were normal. On per-speculum examination, the ectocervix was replaced by a friable growth that bled on touch. A biopsy of the growth was taken and sent for tuberculosis (TB), cartridge based nucleic acid amplification test (CBNAAT), and histopathology. Her CBNAAT was negative, but her histopathology showed numerous epithelioid cell granulomas along with Langhans giant cells and scant central necrosis, suggestive of tuberculosis of the cervix. The patient was sent to a TB clinic and was prescribed anti-tubercular therapy for 6 months. Thus, in any case of infertility in a young female with cervical growth mimicking cervical carcinoma, a differential diagnosis should always be kept in mind.